2013
DOI: 10.2478/vzoo-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Rain-Call Dialects of the Chaffinch, Fringilla coelebs (Fringillidae), in Ukraine

Abstract: Four types of Chaffinch rain-calls were found in Ukraine: “rülsch” - a trill signal widely spread in Europe; “hui” - a whistle signal that occurs in North-Western and Central Europe; “Crimean” whistle signal known only from Crimean peninsula and “Caucasian” signal occurring in Caucasus, Asia Minor and Balkans. Sonograms of rendition versions are given for all of the call types. Distribution of dialects of Chaffinch rain-calls in Ukraine was examined. “Rülsch”- dialect occurs at most of the plane Ukraine and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…). Dialects have been also well documented for the ‘rain calls’ in the Common Chaffinch (Baptista , Haartman & Numers , Tsvelykh & Yablonovska‐Grishchenko ). Sharp dialect borders were also detected in Rufous‐collared Sparrows (Nottebohm , Handford ) and White‐crowned Sparrows (Marler & Tamura ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…). Dialects have been also well documented for the ‘rain calls’ in the Common Chaffinch (Baptista , Haartman & Numers , Tsvelykh & Yablonovska‐Grishchenko ). Sharp dialect borders were also detected in Rufous‐collared Sparrows (Nottebohm , Handford ) and White‐crowned Sparrows (Marler & Tamura ).…”
Section: Discussionmentioning
confidence: 89%
“…Podos and Warren () suggested several scenarios that may cause geographical variations in birdsong and some of them may be relevant to Yellowhammer dialects. The presence of the same dialects in different areas (a phenomenon also observed in Common Chaffinch Fringilla coelebs ‘rain’ calls; Tsvelykh & Yablonovska‐Grishchenko ) may be explained by a rare long‐distance dispersal of males singing that dialect (and its subsequent establishment and spread by cultural transmission). However, independent emergence of the same dialect type cannot be entirely excluded (see Pipek et al .…”
Section: Discussionmentioning
confidence: 90%
“…Different Chaffi nch populations may have radically diff erent rain-calls: throughout the vast species range, several highly distinctive rain-call dialects were found. Comparative analysis of Chaffi nch rain-calls revealed that signals of Balkan birds were drastically diff erent from analogous signals of Chaffi nches from the Crimea, plain Ukraine and Eastern Carpathians but completely identical to signals of Caucasian birds (Tsvelykh, 2011;Tsvelykh, Yablonovska-Grishchenko, 2013). It is assumed that Chaffi nches from the Caucasus and Asia Minor and some of the Balkan regions belong to one geographical population of subspecies Fringilla coelebs caucasica Serebr.…”
Section: Resultsmentioning
confidence: 99%